TINGKAT STRES DAN STRATEGI KOPING MENGHADAPI STRES PADA MAHASISWA TINGKAT PERSIAPAN BERSAMA TAHUN AKADEMIK 2005/2006 - Neti Hernawati (Institut Pertanian Bogor, 2006)
The purpose of this research was to evaluate relationship between stress level with coping strategy and to find out factors affecting stress level among students living in dormitory of IPB. The study site were at Asrama Putri (Girls Dormitory) and Asrama Putra (Boys Dormitory) Bogor Agricultural University. The data was collected from August to October 2005. The primary data included individual characteristic, the resources of stress, level of stress, coping strategy to deal with stress and also the relation between stress level and coping strategy of the student who lived in Asrama Putra (Boys Dormitory) and Asrama Putri (Girls Dormitory) Bogor Agricultural university. The results showed the things that become the factors of stress for new student college, which are never lived out from home before, too much roommates, difficult to interact with surrounding, personal problems, health problems, homesick and financial problems. Most of respondent was experienced high stress level, which is the respondent who get the tendency of emotional stress is larger than they are who get physical stress as a symptoms. The respondent was tended to do problem-focused coping strategy than emotional-focused coping strategy.